Drought stress response in winter wheat varieties - changes in leaf proteins and proteolytic activities - Simova-Stoilova, Lyudmila (Array, 2020)
Radiation mutagenesis has been used in sustainable agriculture as a tool for increasing plant variability and providing new lines for selection. This necessitates a comparison, by using suitable stress markers, of the newly created lines with some well-established varieties, which are stress tolerant or susceptible. Drought is one of the most frequently encountered stresses with deleterious effects on plant performance and crop yield. Winter wheat seedlings (soil cultures at 3–4th leaf stage) from one mutant line (M181/1338K), one drought-tolerant (Guinness) and one sensitive variety (Farmer) were subjected to severe drought stress by water withholding, followed by recovery. Changes in leaf protein profiles, the amount of Rubisco large subunit (RLS), some specific chloroplast proteins such as Rubisco binding protein (RPB), Rubisco activase (RA), the chaperone subunit clpA/C of clp protease, as well as the activities of exo- and endo-proteases were analyzed. At the protein level, some differences were found in the drought response of genotypes – stability of RLS and RBP in M181/1338K and Guinness, diminution of RLS and increase in RBP in Farmer. RA presented strong up-regulation at recovery in Guinness but decreased in content under drought in M181/1338K and Farmer. Increase in ClpA/C level was found in all compared varieties under stress. Strong increase in total proteolytic activity was detected under drought only in Farmer. Inhibitory analysis revealed a predominance of cysteine and serine protease types. Aminopeptidase activities remained higher at recovery in M181/1338K and Farmer. Results are discussed in terms of genotype-linked different stress coping strategies.